2004
DOI: 10.1080/15421400490436430
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the dynamics of a molecular tracer dissolved in liquid crystal homopolymer and copolymer

Abstract: ESR studies were carried out on the rotational dynamics of cholestane molecular tracer dissolved in liquid crystal homopolymer and copolymer from well above T-NI down to below T-g Rheological measurements also provided the flow relaxation properties of the polymer matrices. The distribution functions of molecular sites were determined, and their stability was monitored as a function of thermal history. The different molecular site distributions and cooperativity degrees were compared and discussed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…45 for both R90 and R80 (Table 5). The value is consistent with the R70 case (ξHT(F)=0.52), 60 and shows a possible similarity with the homopolymer case (ξHT(F)=0.61) after the thermal treatment at 358 K. 61 The relatively high value of ξHT(F), together with the clear sensitivity of the probe dynamics to the nematic-to-isotropic transition, located near 1.2Tg, strengthens the hypothesis that the sites experienced by the molecular tracer in these liquid crystalline polymers may be located among the mesogenic side groups. This appears also in agreement with previous observations on a closely related nematic polyacrylate.…”
Section: /36supporting
confidence: 88%
See 1 more Smart Citation
“…45 for both R90 and R80 (Table 5). The value is consistent with the R70 case (ξHT(F)=0.52), 60 and shows a possible similarity with the homopolymer case (ξHT(F)=0.61) after the thermal treatment at 358 K. 61 The relatively high value of ξHT(F), together with the clear sensitivity of the probe dynamics to the nematic-to-isotropic transition, located near 1.2Tg, strengthens the hypothesis that the sites experienced by the molecular tracer in these liquid crystalline polymers may be located among the mesogenic side groups. This appears also in agreement with previous observations on a closely related nematic polyacrylate.…”
Section: /36supporting
confidence: 88%
“…This decreasing trend collocates these 22/36 values between the highest ones, exhibited by homopolymers 61 (ξHT(S)=0.41), and the smallest ones, found in random copolymers with smaller percentage of MA4 counits: ξHT(S)=0.18 in R70 and ξHT(S)=0.13 in R60. 60,63 This could be due to the softening of the "cages", which collectively host the slow reorientational sites, when the number of mesogenic units in the copolymer is lowered. The slow component of the cholestane dynamics in the intermediate-temperature region, because of the poor coupling to the main polymer relaxation, results in low fractionary exponents ξIT(S) (Table 5) in agreement with the ones found in other random PMA4 copolymers.…”
Section: /36mentioning
confidence: 99%
“…The distribution functions of molecular sites were determined, and their stability was monitored as a function of thermal history. The different molecular site distributions and cooperativity degrees were compared and discussed [43]. An extended study of same samples has shown that the copolymer 40/60 (containing 40% of MMA) easily exhibits stable substrates without thermal treatment, necessary in the 30/70 copolymer and the corresponding PMA4 homopolymer [44].…”
Section: Copolymersmentioning
confidence: 99%